Relationship between network structure and ultimate properties in polyurethane during a chain scission process. (July 2022) - Taourit, Sabrina; Le Gac, Pierre-Yves; Fayolle, Bruno
Highlights: During chain scission, a gradual decrease in stress at break is observed. During chain scission, elongation at break first increases and then drops off. Relationships between ultimate properties and crosslink density are proposed. Abstract: To investigate the impact of chain scission on the tensile properties of elastomers, a polyester-based polyurethane was aged in seawater at several temperatures ranging from 40 °C to 90 °C. Before the hydrolysis process, water diffusion was first characterized and described by Fickian behaviour. In terms of temperature dependence, both mass at saturation and water diffusivity followed Arrhenius behaviour. For ageing durations that exceed saturation time, ester bond hydrolysis occurs and leads to chain scission within the polymer network. This chain scission rate could be described using a first-order reaction and followed Arrhenius behaviour with an activation energy of 71 kJ/mol. From a mechanical point of view, hydrolysis leads to large changes in both stress and strain at break. A gradual decrease in stress at break was observed for all ageing temperatures. Nevertheless, strain at break first increases during ageing and then drops off when the crosslink density is below a critical value of 1.25 kg/mol. After considering more than 30 ageing conditions, relationships between the average crosslink density and these ultimate properties were proposed and discussed here.